The Crystallographic and Electronic Phase Diagrams of Yttria-Stabilized Zirconia Model Electrolytes. (30th May 2017) - Götsch, Thomas; Menzel, Alexander; Bertel, Erminald; Stöger-Pollach, Michael; Penner, Simon
Abstract : Yttria-stabilized zirconia model electrolyte systems with four different compositions are analyzed regarding their crystallographic and electronic structure. By investigating the unit cell height, obtained from electron diffraction patterns, it is shown that a phase transformation between the tetragonal and cubic polymorphs takes place between 8 and 9.3 mol%. Furthermore, the direct band gaps are shown to exhibit the same behavior as the lattice parameter, featuring a discontinuity at the phase transition. By measuring the emitted Čerenkov radiation, an electronic transition that is smaller than the band gaps is found, suggesting that localized defect states are present within the band gap, which is in agreement with UV photoelectron spectra.